Rosa BIZARRO, Maria Alfredo MOREIRA, Cristina FLORES. Português Língua Rosa BIZARRO, Maria Alfredo MOREIRA, Cristina FLORES. Português Língua Não Materna: Investigação e Ensino. Lisboa: LIDEL, 2013. 194p. ISBN-978-972-757-928-0 [Recensão] - Duarte, Isabel Margarida (Linguarum Arena, 2018)
.